A Nodule-Localized Small Heat Shock Protein GmHSP17.1 Confers Nodule Development and Nitrogen Fixation in Soybean - Yang, Zhanwu; Du, Hui; Sun, Jingyi; Xing, Xinzhu; Kong, Youbin; Li, Wenlong; Li, Xihuan; Zhang, Caiying (Frontiers in Plant Science, 2022)
Small heat shock proteins (sHSPs) are ubiquitous proteins present in all organisms. sHSPs are not only up-regulated under heat shock as well as other stresses, but also express in unstressed cells, indicating quite diverse functions of sHSPs. However, there is little known about the role of sHSPs in nodulation and nitrogen fixation in soybean. In this study, we cloned a candidate gene of sHSP, GmHSP17.1, from proteome of nodule and analyzed its function in soybean nodulation. We found GmHSP17.1 was a cytosolic protein and preferentially expressed during nodule development. Overexpression of GmHSP17.1 in composite transgenic plants showed increases in nodule number, fresh weight, nodule size, area of infection cells and nitrogenase activity, and subsequently promoted the content of nitrogen and growth of soybean plants. While GmHSP17.1 RNAi lines showed significantly impaired nodule development and nitrogen fixation efficiency. Through liquid chromatography-tandem mass spectrometry (LC-MS/MS), GmRIP1 was identified as the first potential target of GmHSP17.1, and was shown to be specifically expressed in soybean nodules. The interaction between GmHSP17.1 and GmRIP1 was further confirmed by Y2H, BiFC in vivo and pull-down assay in vitro. Furthermore, peroxidase activity was markedly increased in GmHSP17.1 overexpressed nodules and decreased in RNAi lines. As a result, the ROS content greatly decreased in GmHSP17.1 overexpression lines and increased in suppression lines. Taken together, we conclude that GmHSP17.1 plays an important role in soybean nodulation through interacting with GmRIP1. Our results provide foundation for studying the mechanism of nitrogen fixation and for genetics improvement of legume plants.